Household health expenditure and healthcare costs of fishing households in selected coastal areas of San Joaquin, Iloilo. - Flores, Mary Angelie B.
This study aims to look into the expenditure profile, health care alternatives, and significant factors affecting the decision in utilizing and expending for health care of fishing households in San Joaquin, Iloilo. A survey was conducted with 210 household respondents using a questionnaire. Data were analyzed using logit and linear regressions. Findings suggest that households spend most of their income on food and puts health as a mid-tier expenditure priority. Health care alternatives of respondents include self-medication such as taking of herbal medicine and consultation with local traditional healers. Educational attainment, the type of healthcare provider, and the number of ill household members greatly affect the decision of fishing households to utilize professional healthcare while total household expenditure and travel costs influence household health expenditure. By showing the household health expenditure and healthcare cost of these households, this research puts the spotlight on one of the country?s poorest sector, the small-scale fishers, thus increasing awareness of government and healthcare practitioners about the issues concerning their health and healthcare utilization patterns.